Compressibility characteristics and modification effect of coal reservoirs in Longtan Formation, Nanchuan area, southeast Chongqing - Jinxian LIU; Tao GUO; Yatong ZHOU; Dongyang LI; Xiaobo JIN (Shiyou shiyan dizhi)
Fracturing modification is an important method for enhancing the permeability and conductivity in coalbed methane (CBM) wells. To better guide the development and production of CBM wells in Longtan Formation of Nanchuan area, southeast Chongqing, the study comprehensively applied various experimental methods including well logging data, industrial analysis, scanning electron microscopy, polished section observation, and whole-rock analysis. Based on the characteristics of coal rock porosity, roof and floor plate distribution, and gas content, it analyzed the compressibility characteristics of coal reservoirs and their impact on reservoir modification. The study shows that: (1) The coal rocks exhibit characteristics of medium to high evolution degree, medium to high vitrinite content, and medium to low ash content. The primary storage spaces in coal rocks are micropores and fractures, which facilitates gas adsorption. The coal seams are stably distributed, with the floor plate consisting of aluminous mudstone and the roof plate composed of mudstone, which locally transitions to argillaceous limestone and limestone. The assemblage patterns of the coal reservoir and its roof and floor plates, as well as the variations of mineral composition in roof plate, indicate a transitional sedimentary environment between land and sea. (2) Significant differences in mechanical parameters and in-situ stress of coal seams and roof and floor plates were observed, preliminarily indicating good compressibility. Triaxial stress experiments revealed that under high pressures, mechanical parameters of coal seams could exceed those of roof plate, thereby increasing the risk of fracturing. (3) Controlled by the variations of sedimentary conditions in coal measures, the lithological assemblage of the coal seams with the roof plate, and the mineral composition of the roof plate directly affect wellbore stability during horizontal drilling. Mudstone roof plates with high clay mineral content are brittle, prone to fracturing, and susceptible to swelling upon water contact, which are the major causes for spalling risks and impact horizontal well drilling rate. (4) Irregular natural fractures can lead to fracture propagation and fracture height control failure, while regular fractures that align with the direction of maximum principal stress facilitate artificial fracture propagation and contribute to effective reservoir modification.